Socioeconomic overview of long-lived companies in Ecuadorian Coastal Zone 4 - Ojeda Zambrano, Carla de los Ángeles (2024)
The objective of the study is to describe by 2022 the socioeconomic composition of active companies considered as long-lived with an age equal to or greater than 25 years within Zone 4 according to the territorial system of Ecuador.  The analysis is developed through a descriptive and transversal study with an inductive quantitative basis approach carried out through the documentary inquiry in official databases.  From a total of 199 companies analyzed, the investigation shows that none of them exceeds one hundred years and that most of the organizations are microenterprises, which to some extent evidences a stagnation in the growth of their total income.